Influence of passive arm-support exoskeleton on static postural balance in load-holding tasks: effects of supportive force, weight and load location. - Jonathan, Erik; Xiong, Shuping (Ergonomics, 2025)
This study systematically investigated the influence of a passive arm-support exoskeleton (ASE) on static postural balance in load-holding tasks under different weight conditions and load locations, and the relationship between such influence and the exoskeleton's supportive force profile. Using a 3 (exoskeleton interventions) ×3 (weight conditions) ×3 (load locations) within-subjects design, the research found that wearing ASE with supportive force significantly reduced postural sway by 17.84% and 15.19% across all conditions compared to without wearing the exoskeleton and with deactivated support, respectively. These improvements were consistent with subjective assessments. The stability benefits varied with the weight and load location, reflecting the exoskeleton's supportive force profile. Overall, the study suggests that the supportive force from the ASE can enhance static postural balance, with effectiveness dependent on weight conditions and load locations. This highlights the potential of passive ASEs for improving stability and reducing fall risks in work environments.